Women and The City of London in Doris Lessing’s The Diaries of Jane Somers (1984) - Pettersson, Lin Elinor (Universidad de La Laguna, 2014)
This paper examines the feminine perspective of London in Doris Lessing’s The Diaries of Jane Somers (1984). Lessing offers a feminist vision of the city representing London as a stage. Janna, the protagonist, strolls around the city, becoming a flâneuse as she gazes at the spectacle of urban life. Janna’s relationship to the old woman Maudie Fowler enables her to see the different layers of time and space of London and read the city as a palimpsest, a manuscript that shows traces of earlier texts. Lessing blends the theatrical view of city with the palimpsest. Furthermore, nature is not separated from the urban environment, but included as an essential part of the city. The femininity in Lessing’s view of London resides in the combination of theatre, palimpsest and nature.
Keywords: Londres - En la literatura; Doris Lessing; London in literature; London as a stage; Jane Somers; Palimpsest; Flâneuse